Restoration of arm and hand functions via noninvasive cervical cord neuromodulation after traumatic brain injury: a case study. (5th December 2020) - Qian, Qiuyang; Ling, Yan To; Zhong, Hui; Zheng, Yong-Ping; Alam, Monzurul
ABSTRACT: Objectives : To investigate the effects of transcutaneous electrical stimulation (tES) on upper limb functional rehabilitation in a patient with traumatic brain injury (TBI), and to identify the optimum stimulation parameters of tES. Design : A preliminary case study. Methods : Two successive interventions: Phase I–voluntary physical training (vPT) and Phase II – tES along with vPT (tES+vPT). tES was delivered at C3 and C6 cervical regions. Clinical assessments presented the variation of muscle tone and motor functions, before and after each training phase, and evaluated at 1-month follow up after the last intervention. Results : Our results indicate that vPT alone contributed to a release of muscle spasticity of both arms of the patient with no significant improvement of hand function, while tES+vPT further reduced the spasticity of the left arm, and improved the voluntary motor function of both arms. The grip forces were also increased after the tES+vPT treatment. We found that 1 ms biphasic tES at 30 Hz produced optimum motor outputs. Conclusion : The study demonstrates, for the first time, the potential benefits of cervical tES in regard to improving upper limb motor functions in a patient with chronic TBI.